Relationship Between Cognitive Function And Resilience Levels In The Elderly - Nuruli Khalila Nadifatushaliha; Tri Laksono; Muhammad Irfan (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2026)
The elderly are a group that is vulnerable to cognitive decline due to the aging process, which can affect their psychological adaptation and resilience in facing physical, social, and emotional changes. Resilience is an important factor in maintaining the quality of life of the elderly, so the relationship between cognitive function and resilience levels needs to be further studied. Objective: This study aims to determine the relationship between cognitive function and resilience levels in the elderly. Method: This study used an analytical observational design with a cross-sectional approach. Cognitive function was measured using the Montreal Cognitive Assessment (MoCA), while resilience levels were measured using the Connor-Davidson Resilience Scale (CD-RISC). Data analysis included descriptive analysis, Kolmogorov–Smirnov normality test, and correlation test. Results: The results showed that there was a positive relationship between cognitive function and resilience levels in the elderly, but the relationship was not statistically significant (p > 0.05). This indicates that improved cognitive function tends to be followed by increased resilience, but the relationship is not strong enough to be considered statistically significant. Conclusion: The conclusion of this study is that there is a positive but insignificant relationship between cognitive function and resilience levels in older adults. Further research with a longitudinal design is needed, taking into account other supporting factors, in order to obtain a more comprehensive picture of the relationship